2020
DOI: 10.3390/en13174443
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Nanoscale Wettability Effects of Low Salinity and Nanofluid Enhanced Oil Recovery Techniques

Abstract: In this study, enhanced oil recovery (EOR) techniques—namely low salinity and nanofluid EOR—are probed at the nanometer-scale using an atomic force microscope (AFM). Mica substrates were used as model clay-rich rocks while AFM tips were coated to present alkyl (-CH3), aromatic (-C6H5) and carboxylic acid (-COOH) functional groups, to simulate oil media. We prepared brine formulations to test brine dilution and cation bridging effects while selected concentrations (0 to 1 wt%) of hydrophilic SiO2 nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The adhesion resistance of the fluid in the porous medium increases, forming water boundary layers, reducing permeability, increasing water injection pressure, and ultimately hindering injection and reducing oil recovery . The wettability of a rock surface controls the distribution of fluids in pore spaces in rocks. , Wettability is considered the main parameter governing enhanced oil recovery (EOR). If a rock surface is hydrophobic, liquid retention in a porous medium and adhesion resistance are decreased, leading to faster water flow, the injection volume is increased and the injection pressure is reduced to a certain extent . Therefore, the key to solving injection problems is to change the wettability of reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion resistance of the fluid in the porous medium increases, forming water boundary layers, reducing permeability, increasing water injection pressure, and ultimately hindering injection and reducing oil recovery . The wettability of a rock surface controls the distribution of fluids in pore spaces in rocks. , Wettability is considered the main parameter governing enhanced oil recovery (EOR). If a rock surface is hydrophobic, liquid retention in a porous medium and adhesion resistance are decreased, leading to faster water flow, the injection volume is increased and the injection pressure is reduced to a certain extent . Therefore, the key to solving injection problems is to change the wettability of reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when oil droplets are attached to the surface, nanoparticles increase the disjointing pressure because they can be located in their surrounding region. Afekare et al [23,24] employed atomic force microscopy to investigate the oil release mechanisms when SiO 2 nanoparticles are injected in a clay-rich surfaces. The authors found a significant reduction in the adhesion force and adhesion energy: the wettability alteration was controlled by the reduction in nonelectrostatic and interaction force and increasing of the electrostatic repulsion force.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, atomic force microscopy (AFM) with a sharp solid tip has been used to probe properties of rock surfaces relevant to the oil industry, including their topography as well as mechanical and chemical properties. , The AFM tip can also be functionalized with different organic groups (chemical force microscopy) to mimic the interactions between different oil components and the solid substrate. , Intermolecular forces and the adhesion between the chemically modified tips and substrate can be measured with piconewton resolutions, and wettability alterations can be resolved spatially with submicrometer resolutions by using this technique. Chemical force microscopy with its solid tip cannot, however, fully capture the interactions of a liquid droplet with a solid substrate.…”
Section: Introductionmentioning
confidence: 99%